Association of body roundness index with uterine fibroids in women of childbearing age: a cross-sectional analysis of NHANES 1999–2006 - Feng Zhang; Min Liu; Shanshan Hu; Ningying Zhou; Danni Wu; Yuqing Zan; Fei Sun (Lipids in Health and Disease)
Abstract Background and aim Previous studies have shown an association between obesity and uterine fibroids (UF). Body roundness index (BRI) is an anthropometric measure associated with obesity. However, the association with UF has not been thoroughly elucidated, and further investigation is required to explore the possible link. Our study investigated the possible link between BRI and UF in women aged 20 to 44 years, with a view to providing effective scientific evidence for health management and disease prevention in this population. Methods This cross-sectional study analysis included data from 4043 women of childbearing age from the National Health and Nutrition Examination Survey (NHANES) database 1999–2006.We applied multiple regression analysis to study the association between BRI and UF, subgroup analysis was used to ensure broad applicability and representativeness of conclusions, and finally linear correlation between BRI and UF was explored by smooth curve fitting. Results This study involved 4,043 female participants aged 20–44 years, of whom 331 (8.19%) had fibroids. After controlling for all potential confounders, each additional unit of BRI increased the prevalence of UF by 7% (OR = 1.07,95% CI: 1.01,1.12), Sensitivity analysis by dividing BRI into four groups found a 54% increase in the prevalence of UF within the fourth quartile (Q4) of BRI compared with the first quartile (Q1) of BRI (OR = 1.54, 95% CI: 1.08, 2.20).The link between BRI and UF maintained in subgroup analyses. Furthermore, the study showed a linear positive correlation between BRI and the probability of UF prevalence. Conclusions Higher levels of BRI may be linked to a higher prevalence of UF, according to studies conducted on American women of childbearing age. The study’s conclusions highlight how important BRI is for managing and preventing UF.